Religion in uniform: a critique of US military chaplaincy - Waggoner, Edward (Lexington Books/Fortress Academic, 2019)
The first scholarly evaluation of the contemporary US military chaplain corps, and the first to offer not only political and military but also theological analysis, Religion in Uniform shows why the military's chaplaincy is a failing public project, and what Americans can do about it.